Feasibility of Solid Waste Tuna Loin of Yellowfin Thunnus albacares Raw Materials for The Product Diversification - Wayan Kantun Kantun; Andi Adam Malik; Harianti Harianti (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2015)
Indonesia is one country in the world exporters of tuna in the form of fresh, frozen andprocessed. Tuna exported in processed form large enough to leave waste for exporting companies.The purpose of this study was to determine a feasibility study on solid waste exported tuna loin forraw material diversification. This research was conducted in Majene Makassar Strait. The study wasconducted using descriptive exploratory method by taking a sample of 3 times and each samplewas tested 3 times resulting in 9 times of testing for each of the observed variables. Chemical testwhich includes moisture, protein, fat, ash, carbohydrates, and histamine. Microbiological test thatis E. coli, Salmonella and the total number of bacteria. Data were analyzed by descriptive qualitativeand quantitative display via Tables, Graphics and Image in the form of average value. The resultsshowed that the chemical solid waste tuna loin has a water content ranged from 78.34 to 78.78%,protein content ranged from 14.32 to 16.41%, fat ranged from 1.56 to 1.66%, ash content rangedfrom 5.18 to 5. 58%, carbohydrate content ranged from 1.29 to 1.34%, and histamine ranged from2.08 to 3.21 mg / kg. Solid waste microbiologically tuna loin contains E.coli range from 1.2 to 1.9(<2), Salmonella negative and TPC ranged from 1.4 to 1.8 x 105 kol/g. The results of chemical andmicrobiological testing showed solid waste tuna loin still suitable as raw material diversificationproducts.